RESPONS MIKROBA DAN pH TANAH TERHADAP FREKUENSI PENYEMPROTAN INSEKTISIDA DAN DETEKSI RESIDU PESTISIDA DI TANAH - Maudodi, Raz Sayyid; Priatmadi, Bambang Joko; Wahdah, Raihani; Saidy, Akhmad Rizalli (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
The decline in mustard productivity in recent years has been associated with increasing pest pressure and the uncontrolled use of insecticides. This study aimed to evaluate the effects of a neem leaf–based botanical insecticide and the synthetic insecticide methomyl, applied at three spraying frequencies, on total bacteria, total fungi, soil pH, and pesticide residues. The experiment was arranged in a randomized block design with nested treatments and a separate control. The results showed that the control and the treatments did not differ significantly in total bacterial populations, and insecticide type also had no significant effect. Within the nested factor, methomyl applied at a three-day spraying frequency produced the highest total bacterial population and differed significantly from the other treatments. Total fungal populations did not differ significantly across all treatments. Both types of insecticides increased soil pH compared with the control, with a greater increase observed in methomyl; spraying frequencies of six and nine days produced the highest soil pH values. Residue analysis showed that neither neem nor methomyl triggered the accumulation of persistent semi-volatile residues, and the detected chemical traces more closely reflected soil volatilization dynamics rather than the formation of long-term contaminants. Methomyl increased bacterial populations and soil pH as a short-term degradation response, while the botanical insecticide exerted lower ecological pressure due to its rapid degradation and the absence of stable metabolites. These findings confirm the potential of neem as a more sustainable pest management option and provide a scientific basis for determining pesticide application frequencies that are safe for soil conditions.